Einzige autorisierte Original-Aufnahmen aus dem Gefängnis (Ufa-Film): eine Gefangene (Aktrice Anna Kersten)
Einzige autorisierte Original-Aufnahmen aus dem Gefängnis (Ufa-Film): eine Gefangene (Aktrice Anna Kersten).